Long-lasting ceramic composites for surface dielectric barrier discharge plasma actuators - Shvydyuk, Kateryna (2023)
The developed research presents a novel experimental study of the cost-effective MgO-Al2O3, MgO-CaZrO3 perovskite, and thermally stable YSZ ceramic composites for DBD plasma actuators in aerospace applications. This study focuses on the implementation of ceramic DBD plasma actuators for aerodynamic flow control and ice creation mitigation. For this purpose, electrical power consumption analysis, induced flow velocities assessment, and mechanical and thermal characterization were performed. MgO-Al2O3 presented higher induced velocities than its zirconia-based counterparts of up to 3.3 m/s, and lower heat dissipation, achieving a ceiling temperature of 46 ºC, being thereby the best-suited candidate for active flow control mechanisms. In contrast, YSZ had very high-power consumption translated into a maximum surface temperature of 155.4 ºC, establishing itself for ice mitigation. This extensive research evinces that the strategic combination of the developed ceramics’ thermomechanical, thermoelectric, and electromechanical properties allows them to be a promising breakthrough material for DBD plasma actuators.